Dynamic implications of patenting for crop genetic resources - Koo, Bonwoo; Wright, Brian D. (International Food Policy Research Institute, 1999)
In a climate of rapid technological change, it is important to evaluate policies on the innovation incentives that result from the introduction of intellectual property rights as they relate to agricultural genetic resources. In this paper, we use a stylized model of cumulative innovation to explore the dynamics of introducing patent protection with licensing agreements, and then we contrast those results with the comparative-statics viewpoint. We also investigate the dynamic effects of claims on behalf of farmers on the profits of private crop breeders whose output is newly protected by patents. We show that the choices about patent life and licensing share that optimize worldwide dynamic social welfare can be quite different from the values that maximize steady-state social welfare. Further, recognition of farmers’ rights entails a dynamic welfare loss to producers and consumers that is not revealed in a comparative-statics analysis.